A Rare Case of Cervical Epidural Abscess Post Posterior Cervical Laminotomy with Isolation of Neisseria Meningitides Bacteria - Ammar Najim Abood (Institute of Medico-legal Publications Pvt Ltd, 2021)
Spinal epidural abscess is a rare condition, although it requires an urgent surgery to decrease the pressure onthe epidural sac in addition to the other structures of the spinal cannel cord and nerve roots.A 29 years old female entered the clinic with large neck swelling. She also had a history of headache withneck pain, both arm paresthesia with mild fever. Her MRI showed an epidural collection at level of cervical5 to cervical 7 compressing the dural sac narrowing the spinal cannel and extending to the paraspinalintramuscular area in the neck.She had undergone a surgery with a 2cm mid line incision above the swelling mass in order to suck out thepus. In addition, the intermittent Valsalva maneuver was performed to enhance the epidural pus gat out.The culture and sensitivity test to pus indicated a Neisseria meningitides bacterial growth. Penicillin G andcefotaxime as antibiotics were prescribed. Improvement occurred within 2 weeks.Although rare, the isolated Neisseria meningitides spinal epidural abscess requires an urgent treatmentthrough evacuating and decompressing. Spondylodiscitis or collapse may occur, therefore, a surgery forspine correction may be needed, fellow up is recommended in all forms of epidural abscesses.